The Ciclovía in Bogotá a public space of recreation and leisure: environment, health and citizenship (Impetus, 2021)
This document is part of the context of the doctoral research in progress Public leisure spaces: the case of the Ciclovía in Bogotá 1995-2013. For this research, three fundamental pillars were taken on which this space has been working for some decades: citizen culture, collective health and environmental care. His commitment has been recognized in different academic and social events, setting himself up as an example to follow. The organization, administration and logistics carried out by the District Institute of Recreation and Sports (IDRD), allows us to glimpse the benefits.